Feasibility Study for a Child Guarantee: Country report – Finland - Olli Kangas (European Commission, Directorate-General for Employment, Social Affairs and Inclusion Directorate C — Social Affairs, Unit C.3 — Disability & Inclusion., 2022)
In regard to social security in general, and family benefits in particular, Finland is among the big spenders. Spending on social security makes up 32 percent of the GDP, and 11.6 percent of all social spending and 3.7 percent of the GDP are targeted at families and children. These investments are mirrored in Finland's low levels of income poverty and social exclusion among families with children. Finland and the other Nordic countries belong to the cluster of nations with a very low share of deprived children. The same is true for the other target groups (TG) and all the policy areas. In sum, according to comparative EU statistics there are no major problems in Finland. Only a very small fraction of children in the target groups have problems in the policy areas in focus of the study. However, more nuanced analyses, and expert interviews in particular, paint a much darker picture of several policy areas.
Immigrant families do have more problems with regard to overburdened housing costs than other families. Whereas physical healthcare does not seem to be a problem, there are problems with regard to access to mental healthcare. This is a serious problem for all the other TGs as well.
Finland has focused on providing social and educational services to support the welfare of the disabled children and their families. Disabled children have the right to go to the school that is closest to their home. Services should be free of charge, and municipality of residence is responsible for organising these services. Too much depends on the municipality where the child happens to live. If the necessary services are not available at all, or if they are insufficient, children with disabilities can easily fall behind in their education. Children living in institutions include a number of different groups in Finland: disabled, children taken into custody care, other children placed outside of their homes and refugee children. The biggest group of children living in institutions comprises of those children that are placed outside their homes (about 9,000 children). With regard to disabled children, there is a tendency away from institutional care. By now, less than 200 children with developmental disabilities are residing in institutional care facilities. Another group of children living in institutions are refugees who are placed in reception centres (young refugees in reception homes and teenage refugees in group homes) while their asylum application is being processed.
Recommendations:
·       Finland should improve access to health care in general and mental health care in particular.
·       Processing asylum applications must be much faster.
·       More effective measures should be taken to ensure that all children receive enough support for studying at school, and secure the accessibility of basic education and upper secondary and higher education after basic education in spite of disabilities or other personal characteristics.
·       Finland should introduce budget tracking from the perspective of children's rights and welfare, with a view to monitoring the budget allocations for children.
·       Resources for supporting children with specific needs should be fortified in the educational system.
·       Support for children leaving institutions or foster care should be fortified.
·       The coordination of social, health and educational services must be improved.